Estrategias de enraizamiento de genotipos de Brachiaria en suelos ácidos y de baja fertilidad en Colmbia - Ricaurte Oyola, José Jaumer; Rao, Idupulapati M.; Menjivar Flores, Juan Carlos (2007)
In a Typic Haplustox soil in the Altillanura of the Eastern Plains (Llanos Orientales) of Colombia Shoot biomass production was evaluated, during 41 months in 6 Brachiaria genotypes with variable resistance to high Al levels. with two nutrient levels. Moderate and highly Al-resistant Brachiaria genotypes maintained high shoot biomass production in early months of establishment, declined to medium values until 21 months. Root biomass and root length production of Brachiaria genotypes, as well as native savanna grasses, was greater during rainy season, with a high root production in the first 5 cm of the soil. Savanna species and the genotypes B. decumbens CIAT 606 (high Al+3 resistant) produced finer roots and less root biomass than native savanna species. The dry season induced a proportional increase in deeper root length and biomass production compared with rainy season in both moderately and highly Al-resistant Brachiaria genotypes as well as in native savanna species.